Seasonal effects on sex expression in dioecious bryophytes: insights from an oceanic island region - Anabela Martins; Susana Fontinha; Jairo Patiño; Manuela Sim-Sim (Plant Biosystems, 2025)

Sex-specific responses to climate change in unisexual bryophytes - Anabela Martins; Flavien Collart; Jairo Patiño; Manuela Sim-Sim (Biodiversity and Conservation, 2025)

Patterns and drivers of beta diversity across geographic scales and lineages in the Macaronesian flora - Lea Mouton; Jairo Patiño; Mark Carine; Fred Rumsey; Miguel Menezes de Sequeira; Juana María González‐Mancebo; Rosalina Maria de Almeida Gabriel; Olivier J. Hardy; Manuela Sim‐Sim; J. Alfredo Reyes‐Betancort; Flavien Collart; Alain Vanderpoorten (Journal of Biogeography, 2023)
Aim How spatial, historical and ecological processes drive diversity patterns remains one of the main foci of island biogeography. We determined how beta diversity varies across spatial scales and among organisms, disentangled the drivers of this variation, and examined how, consequently, biogeographic affinities within and among archipelagos vary among land plants. Location Macaronesia. Taxon Bryophytes, pteridophytes, spermatophytes. Methods Species turnover and nestedness were compared within and among archipelagos across taxonomic groups. The relationship between species turnover and nestedness, climatic, geological and geographic factors was analysed using generalized dissimilarity models. Results Species turnover, but not nestedness, increased with the geographic scale. This increment decreased from spermatophytes, pteridophytes and bryophytes, wherein the median turnover was less than half that in spermatophytes. Bryophytes exhibited a significantly higher nestedness and lower turnover than spermatophytes. Extant climatic conditions and island age contributed the most to all models but the importance of island age for bryophyte and pteridophyte turnover was marginal. Spermatophyte floras clustered by archipelago, whereas the clustering patterns in pteridophyte and bryophyte floras reflected macroclimatic conditions. Main Conclusions The lower increment of species turnover with spatial scale and the higher nestedness in bryophytes and pteridophytes than in spermatophytes reflect the variation in dispersal capacities and distribution ranges among land plants. Accordingly, extant climatic conditions contributed more to explain turnover in bryophytes and pteridophytes than in spermatophytes, whereas factors associated with dispersal limitations, including island age, geographic distance and archipelago structure, exhibited the reverse trend. The differences in beta diversity patterns, caused by different responses of Macaronesian land plant lineages to the main factors shaping their community composition, explain their different biogeographic affinities. These differences reflect a distinct origin and different mechanisms of speciation among Macaronesian land plant lineages and archipelagos.

Exormotheca martins-loussaoae (Exormothecaceae, Hepaticae), a new species from Cape Verde - Anabela Martins; César Augusto Garcia; Jairo Patiño; Manuela Sim-Sim (Plant Biosystems, 2023)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Integrative taxonomy reveals too extensive lumping and a new species in the moss genus Amphidium (Bryophyta) - Manuela Sim-Sim; Olga M. Afonina; Tereza Almeida; Aurélie Désamoré; Benjamin Laenen; César Augusto Garcia; Juana M. González-Mancebo; Michael Stech (Systematics and Biodiversity, 2017)

Age estimates of Frullania (Frullaniaceae, Porellales) main lineages: another example of rapid and recent diversification in liverwort evolution - Sara E. Silva; Diogo N. Silva; Tereza Almeida; CÉsar A. Garcia; OctÁvio S. Paulo; Manuela Sim-sim (Systematics and Biodiversity, 2017)

Bryophyte conservation on a North Atlantic hotspot: threatened bryophytes in Madeira and Selvagens Archipelagos (Portugal) - Manuela Sim-Sim; Sara Ruas; Susana Fontinha; Lars Hedenäs; Cecília Sérgio; Carlos Lobo (Systematics and Biodiversity, 2014)

Molecular, phytochemical and morphological characterization of the liverwort genus Radula in Portugal (mainland, Madeira, Azores) - Michael Stech; Manuela Sim-Sim; M. Glória Esquível; Leena luís; Susana Fontinha; Carlos Lobo; César Garcia; Soraia Martins; Cristiana Vieira; José Barroso; Luis G. Pedro; A. Cristina S. Figueiredo (Systematics and Biodiversity, 2010)